Iraq and Afghanistan Veterans' Use of Veterans Health Administration and Purchased Care Before and After Veterans Choice Program Implementation - Vanneman, Megan E; Harris, Alex H S; Asch, Steven M; Scott, Winifred J; Murrell, Samantha S; Wagner, Todd H (Medical care, 2017)
The Veterans Choice Program (VCP), enacted by Congress after concerns surfaced about access, enables veterans to receive care outside Veterans Health Administration (VHA) facilities. Veterans who face long wait times, large driving distances, or particular hardships are eligible for VCP. Prior purchased care programs were comparatively limited in scope. We sought to describe utilization of VHA-provided and purchased outpatient care by veterans eligible for VCP before and after VCP implementation. We focused on veterans recently eligible for VHA as they are of particular policy relevance and might have less established care patterns. We identified all Iraq and Afghanistan veterans who were eligible for VCP in 2015. We tabulated their use of VHA and purchased outpatient care for 3 years before (FY2012-2014) and 1 year after VCP implementation (FY2015). Our study population consisted of 214,449 Iraq and Afghanistan veterans who were eligible for VCP due to wait-time, distance, or hardship issues. In the first year of the program, 3821 (2%) of these Iraq and Afghanistan veterans used non-VHA services through VCP. Per capita VHA utilization tended to decline slightly after VCP implementation, but these changes varied by type of outpatient care. There was low uptake of VCP services in the first year of the program. Data from additional years are needed to better understand the impact of this policy.